Factors Affecting Zakat, Infaq And Alms Payments In Gorontalo City (Case Study At Baznas Gorontalo City) - Rahayu Putri Ayu Kalapati; Alfandi Atuna (Global Scientific Publishing, 2023)
Study This aim For analyze factors that can influence payment of Zakat, Infaq and Alms and for know method used in payment of Zakat, Infaq and Alms in Gorontalo City. As for Methodology study This is use study qualitative with studies case . Data collection techniques were carried out with interview in a way depth and observation location research . Whereas technique data analysis was carried out with method examination data validity with use method triangulation . Research result this show that the factors that influence collection zis that is lack of awareness self road heart public in paying zakat, lack of sincerity in spending money, lack of education especially knowledge about the Islamic religion , postpone payment as well as lack of trust public to administering institutions zakat payment . There are methods that can be done used in There are 3 ( three ) ZIS payment methods that is with pay direct to Gorontalo City BAZNAS office , via mobile banking application and can deposit direct to the bank that owns it cooperation with BAZNAS including Bank Sulut Go (BSG), Bank Syariah Indonesia (BSI), Bank Muamalat
Keywords: Zakat; Infaq; Muamalat